Photometry of asteroids (5141), (43032), (85953), (259221), and (363599) observed at Pic du Midi Observatory. Issue 2 (6th April 2018) - Dumitru, B. A.; Birlan, M.; Sonka, A.; Colas, F.; Nedelcu, D. A.
Abstract : These are the first results of an observational program devoted to the complete physical data of asteroids that could produce or feed meteoroid streams. Our results are based on the optical observation at Pic du Midi observatory in April 6–7, 2016 and January 17–18, 2018. We will present the light curve of asteroid (259221) 2003 BA21, associated with Daytime Sextantids (221 DSX) and November θ Aurigids (390 THA); the light curves and colors of asteroid (363599) 2004 FG11, associated with Daytime ζ Perseids (172 ZPE) as well as g  −  r and g  −  i; and the corresponding reflectances for the (85953) 1999 FK21, associated with Daytime ξ Sagittariids (100 XSA). We will also present the colors for two additional objects, namely, (5141) Tachibana and (43032) 1999 VR26.